THE IMPACT OF COMPLEX THERAPY ON QUALITY OF LIFE AND COGNITIVE IMPAIRMENT IN THE REHABILITATION OF PATIENTS WITH CHRONIC CEREBRAL ISCHEMIA - Авров, Максим Владимирович; Алифирова, Валентина Михайловна; Коваленко, Андрей Владимирович (Medicine in Kuzbass, 2018)
Subject. Methods and results of correction of quality of life and moderate cognitive impairment in patients with chronic cerebral ischemia. Objective. The study of the effectiveness of complex treatment in the correction of the quality of life index and cognitive impairment in patients with chronic cerebral ischemia. Material and methods. We examined 100 patients with chronic cerebral ischemia. All patients received standard neurometabolic therapy. In the main group, patients were additionally treated with soft techniques of manual therapy. The quality of life score was assessed using the SF-36 questionnaire, and cognitive status using the frontal dysfunction battery scale, a clock drawing test, a brief assessment scale for mental status, a general deterioration scale, a digital sequence test. Results. In patients with chronic cerebral ischemia, a significant decrease in the quality of life indicator and a violation of cognitive status was found. Field of application. Quality of life issues and cognitive impairment in patients with chronic cerebral ischemia represent one of the most important problems in the rehabilitation of patients. One of the possible areas of rehabilitation of such patients is an integrated approach. Conclusions. Patients receiving complex (drug and non-drug) treatment showed a more significant effect of treatment.